2020
DOI: 10.5336/sportsci.2019-70271
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Injury History in Elite Athletes: Relationship with Kinesiophobia and Effect on Physical Performance

Abstract: ABS TRACT Objective:Considering the psychosocial factors of performance, the injury history will affect the physical performance parameters. Kinesiophobia is one of these factors. Although injuries are effective with motivation factors in athletes, the focus of research is on physical factors. Accordingly the main objective of the study was to investigate the presence of kinesiophobia in elite athletes with and without a history of lower limb injury. The secondary aim was to determine the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…Significantly, the study revealed that a considerable portion of participants reported experiencing fear of movement (kinesiophobia) as well as exercise addiction. Previous research on kinesiophobia among athletes has indicated that those who have sustained sports injuries tend to exhibit higher levels of this fear [30]. Furthermore, there is evidence suggesting that athletes might be more susceptible to exercise addiction [12,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, the study revealed that a considerable portion of participants reported experiencing fear of movement (kinesiophobia) as well as exercise addiction. Previous research on kinesiophobia among athletes has indicated that those who have sustained sports injuries tend to exhibit higher levels of this fear [30]. Furthermore, there is evidence suggesting that athletes might be more susceptible to exercise addiction [12,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Perrot vd., kas-iskelet sistemi ağrısı tanısı ile fizik tedavi alan bireylerdeki hareket korkusunu incelediklerinde; yaşı ileri olanların (50 yaş ve üzeri), daha az fiziksel aktivitede bulunanların, daha fazla ağrı hissedenlerin ve ağrıyı daha az kabullenenlerin daha yüksek seviyede hareket korkusu yaşadıklarını tespit etmiştir. 11 Cinsiyetin 23 daha yüksekte olması sağlıklı grup ile alt ekstremite yaralanması geçiren gruplar arasında hareket korkusu sonuçlarında farkın oluşmamasını sağlamış olabilir. Çünkü aktivite seviyesi orta ya da düşük seviyede olan bireylerin ağrıya verebilecekleri yanıtın 'ağrıdan kaçınma' olması beklenirken 24 , elit düzeydeki sporcuların aynı duruma 'kaçınmaya dayanma' cevabı vermeleri beklenmektedir.…”
unclassified